The determination of critical rest interval from the intermittent critical velocity test in club-level collegiate hockey and rugby players - Fukuda, D. H.; Smith, A. E.; Kendall, K. L.; Cramer, J. T.; Stout, J. F. (The Journal of Strength and Conditioning Research, 2011)
The intermittent critical velocity (ICV) test is used to quantify the relationship between velocity and time to exhaustion, yielding an aerobic parameter (ICV), an anaerobic parameter (anaerobic running capacity [ARC]), and critical rest interval (CRI). Critical rest interval is the theoretical rest period needed to maintain repeated bouts of exercise for an extended period of time without inducing fatigue during intermittent treadmill running. Fourteen collegiate, club-level male participants (mean ± SD; age: 21.4 ± 1.8 years; weight: 82.8 ± 5.9 kg; body fat: 11.8 ± 5.4%; and VO2max: 51.2 ± 2.8 ml/kg/min), primarily hockey and rugby players, completed the ICV test, using 15-second repeated sprints to exhaustion during separate sessions of treadmill running at varying supramaximal intensities. The time and total distance for each running session were used to determine ICV and ARC via linear regression. The CRI was calculated using the relationship between total distance during the ICV test and the number of intervals completed. Mean ICV and ARC (±SD) values were calculated as 4.80 ± 0.3 m/s and 154.1 ± 36 m, respectively. The mean ICV values were significantly different from the mean peak velocity (±SD) (4.67 ± 0.17 m/s) achieved during the VO2max test (p = 0.011). The CRI was calculated as mean ± SD: 33.9 ± 1.9 seconds. Body fat percentage measured by air displacement plethysmography (BOD POD®; r = -0.649; p = 0.012), lean body mass (r = -0.556; p = 0.039), fat mass (r = -0.634; p = 0.015), body weight (r = -0.669; p = 0.006), and relative VO2max (r = 0.562; p = 0.036) were significantly correlated with ICV. The ARC (r = 0.804; p = 0.001) and velocity at ventilatory threshold (r = -0.630; p = 0.016) were significantly correlated with CRI. The ability to quantify CRI, an additional variable derived from the ICV test, provides a possible measure that can be used in the prescription and evaluation of training methods.